2012
DOI: 10.1097/aln.0b013e31827515de
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of High-dose Nebulized Colistin in Ventilator-associated Pneumonia Caused by Multidrug-resistant Pseudomonas aeruginosa  and Acinetobacter baumannii 

Abstract: Nebulization of high-dose colistin was effective to treat VAP caused by multidrug-resistant P. aeruginosa or A. baumannii. Its therapeutic effect was noninferior to intravenous β-lactams associated with aminoglycosides or quinolones for treating VAP caused by susceptible P. aeruginosa and A. baumannii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
1
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(136 citation statements)
references
References 57 publications
5
114
1
16
Order By: Relevance
“…Thus, at this point, the data are mixed regarding whether adding inhaled colistin to systemic therapy improves clinical cure. Importantly, several studies have reported favorable outcomes of patients with ventilator-associated pneumonia caused by highly resistant Gram-negative bacteria, including XDR A. baumannii, treated with monotherapy inhalational colistin without adjunctive systemic therapy (255,259,261,263). However, these results should be viewed cautiously, as cases were nonrandomized leading to a potential selection bias.…”
Section: Current Treatment Optionsmentioning
confidence: 58%
See 2 more Smart Citations
“…Thus, at this point, the data are mixed regarding whether adding inhaled colistin to systemic therapy improves clinical cure. Importantly, several studies have reported favorable outcomes of patients with ventilator-associated pneumonia caused by highly resistant Gram-negative bacteria, including XDR A. baumannii, treated with monotherapy inhalational colistin without adjunctive systemic therapy (255,259,261,263). However, these results should be viewed cautiously, as cases were nonrandomized leading to a potential selection bias.…”
Section: Current Treatment Optionsmentioning
confidence: 58%
“…In contrast, nebulizing polymyxins has the potential to achieve very high concentrations in the lungs while minimizing systemic exposure and toxicity. Numerous investigators have described favorable outcomes of patients with nonbacteremic Acinetobacter pneumonia who were treated with nebulized polymyxins (252)(253)(254)(255)(256)(257)(258)(259)(260)(261). In one case-control study, use of inhaled colistin increased microbial eradication rate from the airways in ventilated patients compared to systemic therapy (257).…”
Section: Current Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, concentrations of formed colistin in the ultrafiltrate were similar at the beginning and end of sampling. Additionally, the patients were treated with nebulized CMS during CVVH and pharmacokinetic sampling, which may complicate the interpretation of colistin plasma concentrations, but inhaled colistin has been shown to have minimal systemic absorption at doses higher than those observed here (31,32). Due to the inherent limitations in the system of care at the U.S. Army Institute of Surgical Re- search, we were not able to ascertain the age of the CVVH filters at the time of sampling.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest, most well-designed cohort to date, 28 patients with VAP due to MDR A. baumannii or P. aeruginosa were treated with inhaled colistin monotherapy in a prospective, observational study (284). These patients were compared to those with MDR VAP treated with inhaled colistin along with an i.v.…”
Section: Nosocomial Pneumoniamentioning
confidence: 99%